Translatio studii i kontakty międzykulturowe w średniowieczu. Słowo o V Kongresie Mediewistów Polskich w Rzeszowie - Trościński, Grzegorz (Tematy i Konteksty, 2016)
Between September 20th and 24th, 2015 Rzeszów hosted the Fifth Congress of Polish Medievalists, which was attended by about 250 scholars of the Middle Ages from all academic centres in Poland and from abroad. The congress theme was “Reception and Rejection. Intercultural Contacts in the Middle Ages”. A large number of papers were presented in 20 thematic sections.One section, no. 17, entitled “Translatio studii in the intellectual and literary culture of the Middle Ages”, was organized by Professor Andrzej Dąbrówka from the Institute of Literary Research of the Polish Academy of Sciences and Grzegorz Trościński, Ph.D. from the Old Polish and Enlightenment Literature Department of the University of Rzeszów. The speakers included philosophers, historians of Polish literature and linguists from several academic centres in Poland. The papers focused on the main intellectual current of the Middle Ages, depicted from various perspectives and shown at different angles. Translatio studii turned out to be multifaceted and long-lasting.